Temporary Immunity of Blackbelly Lambs Reinfected with Trichostrongylus colubriformis - Garduño, Roberto González; Arellano, María Eugenia López; Gives, Pedro Mendoza de; Robertos, Nadia Florencia Ojeda; Canul, Alfonso Juventino Chay (Acta Scientiae Veterinariae, 2016)
Background: Trichostrongylus colubriformis is one of the most prevalent gastrointestinal nematodes of sheep in warm climates. In this nematode species, anthelmintic resistance (AR) has been reported, which has motivated the search for alternative methods to control it. One practice is to increase the immune response level through the selection of animals with natural resistance, such as Blackbelly sheep. The aim of this study was to investigate the response of IgA and IgG in serum and saliva and the level of cells involved in the acquired resistance in Blackbelly lambs after single artificial reinfection with a resistant strain of Trichostrongylus colubriformis. Materials, Methods & Results: Sixteen weaned lambs grazed for one month in nematode-contaminated grasslands. All the lambs were treated with Albendazole and Levamisole; later, they were stabled for two months. After that, eight lambs were re-infected with 6000 larvae of T. colubriformis and other eight lambs remained naturally infected. In addition, eight nematode-free lambs raised in cages, served as negative control. Blood samples were taken fortnightly to determine packed cell volume (PCV, %), plasmatic protein (g dL-1), as well as absolute and differential leukocytes. The eggs per gram of feces (EPG) were recorded. An indirect ELISA against T. colubriformis Ag was performed to determine the IgG and IgA levels. All data were analyzed by repeated measures. The EPG in the re-infected group increased after 34 days (625 ± 287), while in the naturally infected group it remained close to 200 ± 158 throughout the study. The control lambs did not show any infection. The PCV (29.4 ± 3.4 %), basophils (44 ± 74), lymphocytes (8443 ± 2845) and monocytes (77 ± 91) counts were not affected by infection. The IgA OD against T. colubriformis increased significantly after 15 days post-infection (dpi) in the re-infected lambs (1.69 ± 0.5, 80% with regards to standard). With IgG was not possible to distinguish the effect of infection. Discussion: Highly persistent infection of T. colubriformis was observed for at least four months in the naturally infected group despite having been treated with anthelmintics. It is a significant problem because this species has a high prevalence in the region of study and shows anthelmintic resistance. For such reason, is important to evaluate the ability of the animal to develop an immune response. In other study, a natural reduction in the fecal egg count (FEC) was indicated at 100 dpi in the same species, but in the present work, the FEC could not be reduced until around 120 days when the naturally infected lambs were evaluated. The larger number of neutrophils and leukocytes in both the naturally infected and re-infected groups implies a sustained response for a long time. While the higher counts of eosinophils only in the re-infected group were produced as an immediate response to infection with T. colubriformis. Similarly, with a single infection of T. colubriformis, in Santa Ines sheep the infected lambs showed significantly higher levels of serum IgA than the control group. In this case, differences in IgA activity were observed between the re-infected lambs and the other groups at fifteen dpi, but the basal levels of IgA in the naturally pre-infected lambs were maintained at least five weeks after infection. In conclusion, an increase in the peripheral immune response in lambs re-infected with T. colubriformis resulted from the increase in IgA levels in serum and saliva, and increase in the number of peripheral eosinophils, total leukocytes and neutrophils. Re-infected lambs had a higher level of IgA than naturally infected lambs and control lambs, making possible to promote the immune response with a single re-infection with Trichostrongylus colubriformis.